Mechanical mechanism of rock mass slabbing aggravating toppling failure - Cai, Junchao; Lu, Shuqiang; Li, Kan; Wu, Zhongteng; Zhao, Rui; Wang, Junping (Frontiers in Ecology and Evolution, 2023)
Many slabbing rock masses have emerged in hydropower slopes and underground engineerings, with the constructing of basic engineering and resource development projects along the zone of the Belt and Road. The antidip slabbing rock mass is prone to toppling and the degree of slabbing controls the development of toppling deformation. There are few reports on the mechanical mechanism of rock mass toppling deformation after slabbing. Based on the analysis of the genetic conditions of rock mass slabbing, the influence of rock mass after slabbing on toppling deformation was explored by means of mechanics method. The toppling bending deflection (TBD) and the toppling fracture depth (TFD) were selected as the analysis indexes, and the response regularity of slabbing on toppling rock mass was analyzed with examples. The results show that the width and thickness of the slabbing rock mass become narrower and thinner, the toppling bending deflection (TBD) increases, the toppling fracture depth (TFD) decreases, and the toppling deformation and failure intensifies. The TBD is independent of the width of rock mass slabbing under self weight, and the change of TBD is slow when the slab beam slabbing number n of thickness is less than 4 and fast when the slabbing number is above 4. The first TFD decreases fast when w is less then 2.0 m, and it tends to be stable when w is above 2.0 m. The first TFD reduces relatively fast with the thickness t of slab beam decrease. The result of this study can provide a reference for the treatment and evaluation of slabbing rock mass toppling deformation.